Piotr Perzyna – Scientific Conductor within Theory of Thermo-Viscoplasticity - GLEMA, Adam; ŁODYGOWSKI, Tomasz; SUMELKA, Wojciech (Engineering Transactions, 2014)
In this paper, authors reminisce on years of scientific cooperation and achievements on the personality of Piotr Perzyna and his Theory of Thermo-Viscoplasticity, which are displayed from remembrance. All the essence of latin words Master, Doctor, Docent, Professor are in some kind the reflection of the scientific history that has happened during the last 40 years. For every author the shift of 10 to 20 years shows that Piotr Perzyna served with his personality and knowledge for two to three different generations, working with authors as 20/30/50 years younger man. Now, one year after Piotr Perzyna passed away in 2013 (50 years after publishing the basic paper on Theory of Thermo-Viscoplasticity in 1963), the role he has played for authors has become much clearer and conspicuous as well as in a wider context. Like Piotr = Peter = Petrus = Kηφα Professor Perzyna is the rock on which we build. Let it remain not only in memory.